The meanings attributed to community gardening: A qualitative study. (September 2019) - Ong, Michellee; Baker, Amy; Aguilar, Alejandra; Stanley, Mandy
Abstract: Whilst the geographical, sociological, and ecological roles of community gardens have been explored previously, the meanings associated with community gardening are unclear. This narrative inquiry study aimed to understand the meanings attributed to community gardening from an occupational science perspective. Photo elicitation was used alongside narrative interviewing with eight metropolitan South Australian community gardeners. Narrative analysis highlighted five themes: a sense of community; a chance to share; an opportunity to grow; a therapeutic place; ecological contributions. These themes aligned with four dimensions of meaning theorised in the occupational science literature – doing, being, belonging and becoming – with doing and belonging being most evident in our study. Health professionals are encouraged to consider community gardens as places that provide clients with opportunities for enhancing these dimensions of meaning, through engaging in a range of activities, experiencing a sense of belonging and strengthening their identity. By adopting an occupational science lens, these findings provide a new perspective on the importance of engaging in community gardening. Highlights: This study reports on the meanings people attribute to community gardening. Meanings included community, sharing, growth, therapeutic place and eco-systems. The meanings align with dimensions of meaning theorised in occupational science. Community gardens are places that enable doing, being, belonging and becoming. Engaging clients in community gardening may strengthen their belonging and identity.